THE INFLUENCE OF INTERNET MEMES ON ENGLISH VOCABULARY AND GRAMMAR - Azimov Shokhrukh (University Research Base, 2024)
This thesis delves into the profound impact of internet memes on the evolution of English vocabulary and grammar, illuminating the transformative influence of digital culture on the dynamics of contemporary language. Internet memes, as ubiquitous elements of online communication, serve not only as vehicles for humor and cultural commentary but also as catalysts for linguistic creativity and innovation. By synthesizing qualitative and quantitative research methodologies, this study provides a comprehensive examination of how memes contribute to the creation of new linguistic expressions and the modification of existing grammatical structures. It further investigates the integration of meme-derived language into everyday communication, thus underscoring the interplay between digital media practices and linguistic change. Through a detailed analysis of meme content and a survey of language users' attitudes and practices, this thesis reveals the mechanisms by which internet memes influence English, challenging traditional notions of language evolution and standardization. It positions internet memes as a significant force in shaping the future of English, reflecting broader trends in digital communication and cultural expression.